Naskah Al-Qur’an Al-Karim Karya Kiai Abil Fadhal As-Senory - Asif, Muhammad; Nafisantunnisa, Nopi (SUHUF, 2021)
Among the pesantren (Islamic boarding school) community, Abil Fadhal as-Senory is known as a fiqh expert as well as a writer on Arabic theology and Arabic language whose works are taught in pesantren. This study aims to look at the translation of the Noble Qur’ān by Abil Fadhal as-Senory in the context of teaching the interpretation and translation of the Qur’an in pesantren. This study analyzes the translation model and method as well as the ideology in the translation of the Qur’an which is written in Pegon script which is also functioned as a mean of analyzing Arabic grammar in the verses. The translation method used is tarjamah tafsīriyyah (Qur’an translation with exegesis pattern). Theologically, this translation corresponds to the Sunni-Asya’ri theology which is generally adopted by pesantren. This shows that the Javanese translation of the Qur’an is not only related to the process of inter-language interplay, but also represents certain theological teachings. This study also concludes that Abil Fadhal has emphasized the importance of learning the translation of the Qur’an in the pesantren curriculum at the time when the tafsir was still a secondary curriculum at that educational institution.